Experimental activities on Sotacarbo 5 MWth gasification demonstration plant. (1st November 2017) - Calì, Gabriele; Deiana, Paolo; Bassano, Claudia; Maggio, Enrico
Abstract: In the field of coal and biomass gasification for distributed power generation, ENEA and Sotacarbo are developing several activities on demonstration plant scale in order to test gasification technologies for combined production of synthesis gas and electric power in medium and small-scale industrial plants. The Sotacarbo pilot platform has been built up to test different plant solutions at different operating conditions; therefore, a very flexible and simple layout has been designed and constructed. Both demonstration and pilot plants are based on an up-draft, air-blown and fixed-bed gasification process, suitable to be fed with both coal and wood chips. In particular, the demonstration unit of the plant platform includes a 5 MWth gasifier equipped with a wet scrubber for syngas clean up in equicurrent conditions and a flare. This presentation reports some results of the experimental activities related to the start-up of coal and biomass gasification carried out on a demonstration plant at Sotacarbo Research Centre in the South-West of Sardinia (Italy). The aim is to assess the system behaviour and to evaluate the gasification performance. The experimental activity was carried out in order to check the operability of all components and to improve the knowledge of gasifier operation in the different phase of start-up, run and shut down. A characterization of the process was performed and the modalities and key parameters to achieve standard operating conditions were identified. The ultimate aim is to provide useful data so as to improve the system efficiency and to make electricity generation suitable by an internal combustion engine fed by clean syngas. In particular, during the experimental tests different types of fuel were tested: wood chips, Colombian coal, blends of Colombian coal and wood chips. A steady-state simulation model of the gasification process has been developed in the Aspen Plus v.8 simulation environment. The experimental data were used for a first tuning of the model. The validating activity is still going on with newer experimental data. The aim is to realise a model of the plant able to predicts syngas composition, heating value, cold gas efficiency (CGE) and performance at different operating conditions. The model will be a useful tool for future experimental activities.